Taṭbīq manhaj taʿlīm al-naḥw ladā ṭalabat al-mustawā al-khāmis fī Jāmiʿat al-Rāyah Sukabumi - Al Fudiah, Nurul; Solihati, Septia; Bahruddin, Uril; Taufiqurrahman, Arif (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The curriculum is an inseparable element of education. It consists of learning objectives, content, methods, and assessments. In learning Arabic, especially grammar, these four elements are inseparable from the learning process. This study aims to: (1) Describe the implementation of the grammar curriculum in fifth-year students of Al-Raya Sukabumi University (2) Know the inhibiting factors in grammar teaching among fifth-year students at Al-Raya Sukabumi University (3) Know the evaluation of the grammar curriculum among fifth semester students at A r-Raayah University Sukabumi. This research uses a qualitative approach. As for the results of the study: One of the objectives of teaching grammar for the fifth level is to prevent errors in the Qur’an and fiqh and sharia. The learning content is "Al-Tawabi’ and Bab Rafa’ as well as Nasab and Jar" from the explanation of Alfiya Ibn Malik by Muhammad Ali Al-Sultani and the method of education is inductive. As for the assessment, it is with midterm and final exercises and exams. In conclusion, the formulation of educational goals and the selection of content with the help of books and methods in the light of what students are capable of. From this aspect, the ability of lecturers is highlighted to achieve a successful learning process.